2018
DOI: 10.3892/ol.2018.7982
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-37: A crucial cytokine with multiple roles in disease and potentially clinical therapy (Review)

Abstract: Abstract. Interleukin (IL)-37, a new IL-1 family member, has received increasing attention in recent years. In the past decade, it has been determined that IL-37 is expressed in various normal cells and tissues and is regulated by inflammatory stimuli and pro-cytokines via different signal transduction pathways. Recently, it has been found that IL-37 is expressed in a variety of cancers, chronic inflammatory and autoimmune disorders, and exerts anti-inflammatory effects. Moreover, a growing body of literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 87 publications
(140 reference statements)
0
61
0
4
Order By: Relevance
“…Accumulated data have implicated that IL‐37 plays an important role in regulating both innate and adaptive immune responses (Tawfik, Nasef, Omar, & Ghaly, ; Zhao et al, ). In addition, growing bodies of data have revealed that IL‐37 is capable of suppressing the production of inflammatory cytokines, for instance, tumor necrosis factor‐α (TNF‐α) and IL‐6 (L. Wang, Quan, et al, ; L. Wang, Wang, et al, ). A recent study by Yu et al () has shown the evidence that IL‐37 is reduced in GDM placentas and serum and could protect pregnant women from the development of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated data have implicated that IL‐37 plays an important role in regulating both innate and adaptive immune responses (Tawfik, Nasef, Omar, & Ghaly, ; Zhao et al, ). In addition, growing bodies of data have revealed that IL‐37 is capable of suppressing the production of inflammatory cytokines, for instance, tumor necrosis factor‐α (TNF‐α) and IL‐6 (L. Wang, Quan, et al, ; L. Wang, Wang, et al, ). A recent study by Yu et al () has shown the evidence that IL‐37 is reduced in GDM placentas and serum and could protect pregnant women from the development of GDM.…”
Section: Introductionmentioning
confidence: 99%
“…The combined comparison of in silico analysis and in vivo data appear in conflict with regard to the finding that a significant reduction in IL37 expression was observed in PBMCs from MS patients undergoing exacerbation of the disease in the in silico analysis whereas augmented levels of IL37 were observed in the circulation of MS patients suffering an exacerbation. These apparently conflicting results may be explained by the fact that in the in silico analysis only the production of IL37 from PBMC was evaluated, whereas measurement of the circulating levels of IL37 also takes into account the production of IL37 from other non-immune sources including uterus and gastrointestinal cells for example [17]. Although our study is the first to demonstrate increased levels of IL37 during relapses of MS, two previous studies found augmented blood levels of IL37 in Iranian patients suffering from RR-MS and NMO.…”
Section: Discussionmentioning
confidence: 99%
“…IL37 is a cytokine belonging to the IL1 family that was originally discovered by in silico research [15]. IL37 can be found in the cytoplasm and nucleus [16] and is detectable in many human cells, including monocytes; natural killer (NK) cells; stimulated B cells; and tissues such as thymus, bone marrow, lymph nodes, colon, lung, and uterus [17]. The human IL37 gene is located on chromosome 2 and undergoes alternative splicing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been discussed that such a biological function of interleukin-37 could be captured as a clinically successful therapeutic target for the treatment of periodontal inflammation and cancers. 92,93 To explore other similarities between shared epigenome alterations in both periodontitis and cancer, methylation-specific PCR for E-cadherin and cyclooxygenase-2 was performed. 94 while in the breast neoplastic tissue, the gene-silencing detection rate was 38% and 35%, respectively.…”
Section: Peri Odontal Pathog En S and Infl Ammatory Re S P On S E Pmentioning
confidence: 99%